Development Of Traditional Culinary Tourism In Purworejo Regency, Central Java - Sukarno Wibowo (Journal Of Social Science (JoSS), 2023)
This research was compiled to identify the potential for developing local culinary products in building tourism development, especially culinary tourism in Purworejo Regency, Central Java Province. Local culinary creations in some places can positively impact the local economy. Good management can also positively affect the preservation of the local environment and culture. The topic was chosen because of the potential for developing local culinary tourism in Purworejo regency as a district whose area is very strategic in the province of Central Java, where local culinary products are expected to significantly impact the development of local culinary tourism in Purworejo Regency. The type of research conducted by researchers is qualitative descriptive research. Redana (2006: 137) describes descriptive qualitative research. It is a study designed to obtain information about symptoms' state when the investigation involves the local community, local government, tourists and culinary industry players in Purworejo Regency. Data analysis uses qualitative and interpretive descriptive analysis. Qualitative data analysis is the compression of data through the development of classification methods. It is a time series classification system that includes a collection of collected information and systematically reveals their relationships. This research is expected to be a commitment or thought in creating arrangements for increasing traditional culinary tourism in Purworejo Regency, Central Java.